2015
DOI: 10.11113/jt.v75.5214
|View full text |Cite
|
Sign up to set email alerts
|

Flight Performance of Various Blended Wing-Body Small Uav Designs

Abstract: Currently there are four BWB designs that have been tested in the LST-1 wind tunnel at Flight Technology and Test Centre (FTTC), UiTM since 2005. The objective of this paper is to analyse their flight performance of these four BWB UAVs in terms of airspeed flight envelope, endurance, range and rate of climb as a function of the number of batteries and to determine the optimal number of batteries to be carried for 1-hour endurance mission and 3-hour endurance mission. The targeted cruising-loitering airspeed mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[11] Of particular interest in this study is Baseline-VII design that is developed by FTTC based on the cranked-wing flying-wing configuration. This BWB UAV design is estimated to have maximum lift-todrag ratio of 2.19 when cruise flying (i.e., at angle of attack of roughly 0°) [12]. However, it is strongly believed that its aerodynamic performance can be further improved by optimizing its planform shape design.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Of particular interest in this study is Baseline-VII design that is developed by FTTC based on the cranked-wing flying-wing configuration. This BWB UAV design is estimated to have maximum lift-todrag ratio of 2.19 when cruise flying (i.e., at angle of attack of roughly 0°) [12]. However, it is strongly believed that its aerodynamic performance can be further improved by optimizing its planform shape design.…”
Section: Introductionmentioning
confidence: 99%
“…Since September 2005, UiTM has started a research on BWB-UAV [9]. There were several studies that had been carried out on BWB using CFD, wind tunnel, and finite element method [10].…”
Section: Introductionmentioning
confidence: 99%
“…Blended Wing-Body (BWB) aircraft has the potential to be more efficient than current conventional configuration [1]. Various designs of small BWB UAVs have been studied in past 13 years in Universiti Teknologi Mara and found that not all BWB designs are efficient because aerodynamic efficiency depends on many factors [2]. However, compared to the conventional aircraft with separated fuselage and wing, a Blended Wing-Body aircraft design has proven to be able to generate more lift, less parasitic drag, and improve fuel efficiency to more than 20%.…”
Section: Introductionmentioning
confidence: 99%